Implementation and outcomes of the school health programme in Ditsobotla - Keothaile, Kelebogile Joyce (My University, 2016)
The objective of the South African Integrated School Health Programme is to improve health status of learners at schools. Health programmes have been implemented through the integrated school health programme at schools in South Africa since 2012. Targets were set to monitor the implementation of the programme in provinces. The North West Province did not reach its targets for the health programme between 2014 and 2015. A qualitative study was conducted to investigate barriers to implementation of the programme in Ditsobotla sub district. A sample of twenty five participants was selected from a group of teachers, principals and school governing body at ten schools, nurses, education managers, and NGO. In-depth interviews and focus group discussions were conducted. The main findings were that learners were not able to utilize the integrated school health programme service because parents did not give consent. The programme did not have enough dedicated school health programme service providers. Consequently the study recommends that more advocacy sessions should be conducted with the key stakeholders. This study can form a basis for further research seeking to improve the integrated school health programme in the North West Province.
A research report submitted to the Faculty of Management, University of Witwatersrand, in 50% fulfilment of the requirements for the degree of Master of Management (in the field of Public and Development Management) September 2016
Keywords: School health services--South Africa; School health services--Government policy--South Africa